Supporting Frontline Service Providers Working with Persons Experiencing Homelessness: A Scoping Review - Modanloo, Shokoufeh; McMenemy, Claire; Gifford, Wendy; Ali, Shahnaz Shahid; Wazni, Liquaa; Onigbinde, Eunice; Balli, Trannum; Patel, Arrah; Sikora, Lindsey (International Journal on Homelessness, 2026)
Homelessness is an escalating global issue, often rooted in significant trauma, which increases the risk for frontline workers of vicarious trauma that adversely impacts their well-being and work environment. This scoping review aimed to map existing interventions designed to support the well-being of frontline workers in the homelessness sector, highlighting their characteristics, objectives, and outcomes. Following the six-step framework by Arksey and O’Malley, refined by Levac et al. and the Joanna Briggs Institute, we conducted a narrative thematic analysis of 17 studies encompassing 1,679 frontline workers. The identified interventions addressing learning and development opportunities, therapy and consultation, supervision and mentorship, team building and networking, financial support, peer group support, administrative assistance, and self-care strategies. Reported outcomes of interventions included improved knowledge, skills, and self-efficacy; increased job satisfaction; stronger collaboration and sense of belonging; reduced burnout and staff turnover; advocacy for policy changes; and overall improvement in worker well-being. From the narrative analysis of intervention’s components and outcomes, four key themes emerged: (i) tailored training equips frontline workers to prevent and manage vicarious trauma; (ii) multidisciplinary teams benefit both clients and frontline workers; (iii) timely consultation and supervision reduce burnout and turnover; and (iv) administrative and leadership support enhances frontline worker well-being. These findings highlighted that strengthening the homelessness workforce requires a coordinated, cross-sectoral approach involving capacity-building through tailored training, leadership support via supervision and consultation, and appropriate financial incentives. Implementing comprehensive, systemic support fosters a healthier workforce and enables frontline providers to deliver more effective, trauma-informed care. This review provides a comprehensive overview of strategies to support frontline workers serving people experiencing homelessness.